Modelling and analysis of small signal for multi-machine parallel system based on droop control. (2018) - Chan, Xue
Microgrid system based on multi-machine parallel connection has complex structure and various connection modes. In the process of grid-connected splitting, because of the frequency and voltage deviation between sub-microgrid, it will produce large electric power at the PCC point, which will impact the multi-machine microgrid system and affect the dynamic stability of the system. In order to solve the problem of control accuracy and dynamic stability in this such kind of process, considering the voltage drop and voltage phase angle offset of long-distance lines, an improved droop control method is proposed based on the parallel structure of multiple microgrid, the droop control accuracy is optimised, at the same time the corresponding small signal model is established for parameter optimisation, and the simulation model of improved droop control is established on MATLAB/Simulink. The simulation results verify the rationality and effectiveness of the improved control strategy.